Wear analysis of treated Duplex Stainless Steel material by carburizing process – A review. (2020) - Subbiah, Ram; Vinod Kumar, V.; Lakshmi Prasanna, G.
Abstract: A review about the effect of carburizing on Duplex Stainless Steel are analysed in this paper. The focus is kept on the expanding the hardness and wear-ability without losing corrosion resistance could essentially widen its applications. These heat-treated materials were analysed under with respect to different metallographic tests and mechanical tests. The most widely used metallographic tests like X-Ray Diffraction, Scanning Electron Microscope, and mechanical tests like tensile & hardness tests. The paper explains structural and physical changes of Duplex Stainless Steel after heat treatment process.